TO THE PROBLEM OF MODELING THE AERODYNAMICS OF SURFACE TRANSPORTATION VEHICLES - Sokhatsky, A. V. (Systems and Technologies, 2022)
The article deals with the problems of modeling the aerodynamics of surface high-speed vehicles of winged layout moving at a short distance from the water surface. To support them in the air, the screen effect formed under the influence of proximity to the water surface should be used. The effect of ground proximity is observed in air transport in the takeoff and landing modes of aircraft. The proximity of the ground affects the formation of the aerodynamic characteristics of vehicles. Today, the study of the aerodynamics of advanced vehicles moving near the underlying surface is possible using the following approaches: full-scale tests; modeling on special tracks; wind tunnel modeling. Full-scale tests are usually used at the final stages of vehicle development. simulation on special tracks is associated with the complexity of obtaining aerodynamic characteristics and is not widely used. The most suitable is modeling using wind tunnels. The current level of equipment of experimental laboratories allows for correct aerodynamic studies of aircraft. However, when modeling aerodynamic processes around vehicles moving near the interface, complex problems arise with reproducing the conditions of motion dynamics. The paper describes in detail the methods of studying the influence of the proximity of the ground on the formation of aerodynamic characteristics of vehicles in wind tunnels. These include: a method using a fixed plate; a method of mirroring the model; a method of suction or blowing the boundary layer; a method using a moving belt. The possibility of their use for modeling the aerodynamics of high-speed surface vehicles of winged layout is evaluated. When modeling the flow of high-speed vehicles moving near the water surface, a number of difficulties arise due to the realization of real flow conditions, namely, taking into account the dynamics of the water surface. Ideally, relative motion is realized between the vehicle and the water surface. The review of methods used in modeling the aerodynamics of vehicles over a solid screen proved to be of little use for high-speed winged vehicles moving at a short distance from the water surface. Ensuring the similarity of relative motion is an extremely difficult task. It requires a reasonable analysis of physical processes and the search for ways to develop physical and mathematical models suitable for use in the design of high-speed surface vehicles with wing arrangement. These models should range from simple engineering techniques to techniques based on the full and averaged Navier-Stokes equations.